Consumer Preference Analysis On Thai Cassava Sauce With Varying Coconut Milk Types - Ivy Dian Puspitasari Prabowo; Mashita Rafflesia Mustofa (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
This study aimed to analyze consumer preferences for Thai cassava sauce using three types of coconut milk: fresh coconut milk, instant liquid coconut milk, and instant powdered coconut milk. Sensory evaluation was carried out using a 5-point hedonic scale involving 30 untrained panelists. The evaluated sensory attributes included taste, aroma, and appearance. The collected data were analyzed using analysis of variance (ANOVA) with a significance level of α = 0.05 to determine differences in consumer preference among treatments. The results showed that Thai cassava sauce prepared with instant liquid coconut milk obtained the highest average scores for all sensory attributes, including taste (4.60), aroma (4.50), and appearance (4.36). Meanwhile, fresh coconut milk showed moderate acceptance, while instant powdered coconut milk received the lowest scores for most sensory attributes. These findings indicate that the use of instant liquid coconut milk produces Thai cassava sauce with the highest level of consumer acceptance compared to fresh coconut milk and instant powdered coconut milk.